Manipulation of the Sphingolipid Rheostat Influences the Mediator of Flow‐Induced Dilation in the Human Microvasculature - Mary E. Schulz; Boran Katunaric; Joseph C. Hockenberry; David D. Gutterman; Julie K. Freed (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Elevated levels of ceramide, a sphingolipid known to cause a transition from nitric oxide (NO)– to hydrogen peroxide–dependent flow‐induced dilation (FID) in human arterioles, correlate with adverse cardiac events. However, elevations of ceramide are associated with changed concentrations of other sphingolipid metabolites. The effects of sphingolipid metabolites generated through manipulation of this lipid pathway on microvascular function are unknown. We examined the hypothesis that inhibition or activation of the ceramide pathway would determine the mediator of FID. Methods and Results Using videomicroscopy, internal diameter changes were measured in human arterioles collected from discarded adipose tissue during surgery. Inhibition of neutral ceramidase, an enzyme responsible for the hydrolysis of ceramide, favored hydrogen peroxide–dependent FID in arterioles from healthy patients. Using adenoviral technology, overexpression of neutral ceramidase in microvessels from diseased patients resulted in restoration of NO‐dependent FID. Exogenous sphingosine‐1‐phosphate, a sphingolipid with opposing effects of ceramide, also restored NO as the mediator of FID in diseased arterioles. Likewise, exogenous adiponectin, a known activator of neutral ceramidase, or, activation of adiponectin receptors, favored NO‐dependent dilation in arterioles collected from patients with coronary artery disease. Conclusions Sphingolipid metabolites play a critical role in determining the mediator of FID in human resistance arterioles. Manipulating the sphingolipid balance towards ceramide versus sphingosine‐1‐phosphate favors microvascular dysfunction versus restoration of NO‐mediated FID, respectively. Multiple targets exist within this biolipid pathway to treat microvascular dysfunction and potentially improve patient outcomes.